The Role Of Artificial Intelligence In Training Cadets - Xamdamov, Alisher Samijonovich (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article examines the role of artificial intelligence (AI) in cadet training within higher military and professional education institutions. The research results show that AI tools better support personalized learning and cognitive load management and competency-based assessment methods used in cadet training settings.